2014
DOI: 10.1162/jocn_a_00659
|View full text |Cite
|
Sign up to set email alerts
|

The Subthalamic Nucleus Contributes to Post-error Slowing

Abstract: Abstract■ pFC is proposed to implement cognitive control via directed "top-down" influence over behavior. But how is this feat achieved? The virtue of such a descriptive model is contingent on a mechanistic understanding of how motor execution is altered in specific circumstances. In this report, we provide evidence that the well-known phenomenon of slowed RTs following mistakes (post-error slowing) is directly influenced by the degree of subthalamic nucleus (STN) activity. The STN is proposed to act as a brak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 44 publications
8
45
0
Order By: Relevance
“…Regarding the putative target of these frontal nodes, two other studies of PES recorded the STN-LFP in DBS patients (Cavanagh et al, 2014; Siegert et al, 2014). Both studies showed that STN activity was increased following errors, and related to PES on the next trial (the studies differ slightly in the time window at which they identify STN activity that predicts PES; Siegert et al showed that the phase-locked LFP at around 300ms following the erroneous response correlated with PES, while Cavanagh et al showed that the event-related spectral perturbations in the theta frequency immediately before the next response related to PES).…”
Section: Role Of Global Stopping Network In Slowing After Unexpected mentioning
confidence: 99%
“…Regarding the putative target of these frontal nodes, two other studies of PES recorded the STN-LFP in DBS patients (Cavanagh et al, 2014; Siegert et al, 2014). Both studies showed that STN activity was increased following errors, and related to PES on the next trial (the studies differ slightly in the time window at which they identify STN activity that predicts PES; Siegert et al showed that the phase-locked LFP at around 300ms following the erroneous response correlated with PES, while Cavanagh et al showed that the event-related spectral perturbations in the theta frequency immediately before the next response related to PES).…”
Section: Role Of Global Stopping Network In Slowing After Unexpected mentioning
confidence: 99%
“…For example, EEG signatures that index successful motor inhibition in stop‐signal‐type tasks (Kok, Ramautar, De Ruiter, Band, & Ridderinkhof, ; Wessel & Aron, ) share neural generators with parts of the neural activity after errors (Wessel, ; Wessel & Aron, ; Wessel, Jenkinson et al, ), which suggests that they have a common neural generator (Onton, Westerfield, Townsend, & Makeig, ; Wessel, ). Furthermore, the subcortical STN, a core part of the purported inhibitory function of the frontobasal ganglia network, exhibits increased local field potential activity after errors (Cavanagh, Sanguinetti, Allen, Sherman, & Frank, ; Siegert et al, ) and unexpected events in general (Bockova et al, ; Wessel, Jenkinson et al, ). Lastly, just like action stopping (N. Swann et al, ), both action errors and unexpected action outcomes show increased frontocentral to right frontolateral beta‐frequency EEG coherence (Wessel, Ullsperger et al, ).…”
Section: Section Iii: An Adaptive Orienting Theory Of Error Processingmentioning
confidence: 99%
“…In addition to this rapid cortically-mediated form of adaptation, evidence suggests that strategic adjustments in decision threshold are achieved via activity-dependent plasticity in the connections between STN and GPe [24,58] . In the current study, adaptive changes in the boundary height accounted for the observed post-error slowing in responses following failed stop trials, motivated by neuroimaging and electrophysiological evidence STN-mediated slowing of responses [9,17,26] . For simplicity, boundary adaption was restricted to being unidirectional -increasing after a stop-error and decaying back to, but never below, its original value.…”
Section: Drift-rate: Dopaminergic Modulation Of Corticostriatal Pathwaysmentioning
confidence: 95%